DESIGN OF WIDE BAND CMPA - Mahendra Pal Verma, P.K. Singhal (International Journal of Research Science and Management, 2014)
In this paper we are going to design CMPA (Circular Microstrip Patch antenna), and then tried to enhance its bandwidth and radiation efficiency, and other related antenna parameters. We have enhanced its parameters by changing the dimensions of slot of circular microstrip patch antenna.